Phytochemical profile and antimicrobial activity of individual frond extracts of Menisorus pauciflorus, Pteris catoptera, Conniogramme africana and Antrophyum mannianum - Herbert Nuwamanya; Ben Lukubye; Grace Kagoro-Rugunda; Clement Olusoji Ajayi; Raphael Wangalwa; Eunice Apio Olet (BMC Complementary Medicine and Therapies)
Abstract Introduction Ferns have potential antimicrobial compounds but are understudied compared to higher plants. This limits our knowledge of their phytochemical composition and antimicrobial properties, despite their traditional use to treat various ailments. Therefore, this study profiled the phytochemical composition and evaluated the antimicrobial activity of four fern species, namely; Menisorus pauciflorus (Hook.) Alston, Pteris catoptera (Kunze.), Conniogramme africana (Hieron.) and Antrophyum mannianum (Hook.). Methods Fern fronds were collected from Kalinzu Central Forest Reserve (KCFR), cleaned with distilled water, and dried under shade at room temperature for two weeks. Dry fronds were ground using an electric blender into a powder and extracted by means of infusion and cold maceration, using distilled water and 70% ethanol as extraction solvents, respectively. Preliminary qualitative screening and a UV-VIS-spectrophotometer were used for phytochemical profiling by recording the presence (+) or absence (-) and quantities of the selected phytochemical classes, respectively. The antimicrobial activity (zones of inhibition) was determined by Agar well diffusion assay while the minimum inhibitory concentrations were determined using micro-broth dilution in 96-well microplates. The minimum bactericidal concentrations and minimum fungicidal concentrations were determined by subculturing technique. Results Fern extracts contain various phytochemical compounds, such as phenols, tannins, saponins, anthraquinones, terpenoids, and flavonoids, with phenols being the most abundant. The antimicrobial activity of both water and ethanol extracts was higher against Escherichia coli and Staphylococcus aureus and lower against Candida albicans. The antibacterial activity was generally greater against E. coli than against S. aureus. The ethanolic extract of A. mannianum had the lowest minimum inhibitory concentration (3.91 mg/mL) and minimum bactericidal concentration (7.81 mg/mL) against E. coli. The A. mannianum aqueous and ethanol extracts, and the M. pauciflorus ethanol extract had the lowest minimum fungicidal concentration (125 mg/mL) against C. albicans. The C. africana ethanol extract at various concentrations (1000, 500, 250, and 125 mg/mL), produced larger inhibition zones against S. aureus (up to 32.67 mm) than did ciprofloxacin (20.77 mm). Conclusions All the M. pauciflorus, P. catoptera, C. africana, and A. mannianum extracts presented variable secondary metabolite contents, but the concentration of phenols was greater than that of flavonoids and saponins. The extracts possess antimicrobial bioactive agents but weak activity against E. coli, S. aureus and C. albicans. We recommend more studies on the effect of these fern extracts on other bacterial and fungal strains to prove their antimicrobial potential on various pathogenic bacteria and fungi.